Challenges in accessing routinely collected data from multiple providers in the UK for primary studies: Managing the morass. - Lugg-Widger, Fiona V; Angel, Lianna; Cannings-John, Rebecca; Hood, Kerenza; Hughes, Kathryn; Moody, Gwenllian; Robling, Michael (International Journal of Population Data Science, 2018)
Introduction Researchers are increasingly using routinely collected data in addition to, or instead of, other data collection methods. The UK government continues to invest in research centres to encourage use of these data, and trials and cohort studies utilise data linkage methods in the follow-up of participants. This does not come without its limitations and challenges, such as data access delays. Objective This paper outlines the challenges faced by three projects utilising individual-level routinely-collected linked data for the longer-term follow-up of participants. Methods These studies are varied in design, study population and data providers. One researcher was common to the three studies and collated relevant study correspondence, formal documentary evidence such as data sharing agreements and, where relevant, meeting records to review. Key themes were identified and reviewed by other members of the research teams. Mitigating strategies were identified and discussed with a data provider representative and a broader group of researchers to finalise the recommendations presented. Results The challenges discussed are grouped into five themes: Data application process; Project timelines; Dependencies and considerations related to consent; Information Governance; Contractual. In presenting our results descriptively we summarise each case study, identify the main cross-cutting themes and consider the potential for mitigation of challenges. Conclusions We make recommendations that identify responsibilities for both researchers and data providers for mitigating and managing data access challenges. A continued conversation within the research community and with data providers is needed to continue to enable researchers to access and utilise the wealth of routinely-collected data available. The suggestions made in this paper will help researchers be better prepared to deal with the challenges of applying for data from multiple data providers.